Rekomendasi Pemetaan Keahlian Siswa Terhadap Spesifikasi Lowongan Kerja pada Sistem Bursa Kerja Khusus Menggunakan Metode SAW Di SMK - Nanda Riski Septania; Hakkun Elmunsyah; Utomo Pujianto (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2019)
This study aims to produce recommendations in the form of a list of job vacancies in accordance with the expertise of students. The model used in research and development of student expertise mapping recommendations is the waterfall. The testing technique used is black box testing, which is used to test the system's functionality. The product was validated by two experts, namely Expert I and Expert II. The results of the validation carried out by expert I and expert II each received a 100% eligibility percentage. Then from the product trial results obtained a percentage of eligibility 97%. These results indicate that the level of product eligibility is valid because it exceeds the minimum limit of 76% for valid criteria, so the product can be said to be feasible and can be used.